Морфологічний стан судинного русла шишкоподібної залози щурів за умов гострого стресу та цілодобового освітлення - Пшиченко, Вікторія; Pshychenko, Victoria (Східноєвропейський національний університет імені Лесі Українки, 2014)
Проведені дослідження щодо з’ясування особливостей екстраорганного кровоносного русла шишкоподіб¬ної залози щурів і морфологічних проявів реологічних властивостей крові після п’ятигодинного іммобілізацій¬ного стресу та гіпофункції шишкоподібної залози. Установлено, що в кровоносних судинах венозного типу відбуваються порушення кровотоку внаслідок адгезії еритроцитів, сепарації крові, некрозу та лізису еритроци¬тів, а також порушення цілісності судинної стінки. З’ясовано, що ці морфологічні порушення супроводжують¬ся пригніченням функціональної активності шишкоподібної залози. Conducted a study on the features of the vascular bed of the pineal gland of rats and morphological manifestations of the rheological properties of blood after 5-hour immobilization stress and hypofunc¬tion of the pineal gland. Revealed that the venous vessels, which are closely adjacent to the capsule of the pineal gland, there are discontinuities of the vascular wall, accompanied plasmorrhages and edema, as well as the phenomena of blood separation, necrosis and lysis of erythrocytes. In venous vessels located at a considerable distance from the pineal gland capsule marked blood separation conditions, the adhesion of erythrocytes and their attachment to the inner surface of the vascular wall. In the arterial bloodstream link pineal gland revealed a uniform filling of the lumen formed elements of the blood vessels. Established morphological abnormalities in the state of the vascular bed indicate suppression of functional activity of the pineal gland, due to circulatory disorders in the venous vessels.
Morphological State of the Vascular Bed of the Pineal Gland of Rats Under Stress, and Permanent Lighting
Keywords: шишкоподібна залоза; іммобілізаційний стрес; формені елементи крові; адгезія еритроцитів; ендотелиоцити; the pineal gland; immobilization stress; blood cells; red blood cell adhesion; endothelial cells